Impact of Internal Marketing on Organizational Performance: A Field Study of Islamic Banks in Sana’a - Abdullateef Musleh Ayedh; Fatima Mohammed Saghir Al-Osimi (University of Science and Technology, Sana’a, Yemen, 2023)
This study aimed to identify the impact of internal marketing on organizational performance in Islamic Banks in Sana’a. To achieve this, the study adopted the descriptive analytical method. Four banks represented the study population, which included (630) individuals. A questionnaire was distributed to a sample of (242) participants who were selected, using the stratified non-probable sampling method; however, only 164 questionnaires were valid for analysis. The data were analyzed with the help of SPSS. A set of descriptive and inferential statistical techniques were used to assess the study questions and test its hypotheses. The study results revealed that there was a high level of interest in the banks about the realization of organizational performance, whereas the level of practicing internal marketing was medium. There was a disparity in the effect of internal marketing on organizational performance, where the most effective one was the dimension of internal communication, followed by training, motivation, and empowerment. The study proposed a number of recommendations, including paying more attention to the various dimensions of internal marketing, which would lead to increasing the effectiveness of organizational performance, especially the internal communication factor as it is the most effective factor.